2017
DOI: 10.3847/1538-4357/aa9380
|View full text |Cite
|
Sign up to set email alerts
|

Electron and Proton Heating in Transrelativistic Magnetic Reconnection

Abstract: Hot collisionless accretion flows, such as the one in Sgr A * at our Galactic center, provide a unique setting for the investigation of magnetic reconnection. Here, protons are non-relativistic while electrons can be ultra-relativistic. By means of two-dimensional particle-in-cell simulations, we investigate electron and proton heating in the outflows of trans-relativistic reconnection (i.e., σ w ∼ 0.1 − 1, where the magnetization σ w is the ratio of magnetic energy density to enthalpy density). For both elect… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
134
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 131 publications
(145 citation statements)
references
References 48 publications
(71 reference statements)
9
134
0
Order By: Relevance
“…This prescription heats electrons and ions equally and only in highly magnetized regions, resulting in cooler jet regions with less emission than the disk. In total, Chael et al (2018a) presented four simulations spanning the two heating prescriptions considered ("Howes" or "H" for the turbulent cascade prescription of Howes 2010 and "Rowan" or "R" for the reconnection prescription of Rowan et al 2017) and two values of the dimensionless black hole spin (a = 0 for "Lo", and a = 0.9375 for "Hi"). Figure 10 shows that all four models presented in Chael et al (2018a) fit the 1.3 mm constraints and mostly fit the 3 mm image-domain constraints.…”
Section: Constraints On Accretion Flow and Jet Modelsmentioning
confidence: 99%
“…This prescription heats electrons and ions equally and only in highly magnetized regions, resulting in cooler jet regions with less emission than the disk. In total, Chael et al (2018a) presented four simulations spanning the two heating prescriptions considered ("Howes" or "H" for the turbulent cascade prescription of Howes 2010 and "Rowan" or "R" for the reconnection prescription of Rowan et al 2017) and two values of the dimensionless black hole spin (a = 0 for "Lo", and a = 0.9375 for "Hi"). Figure 10 shows that all four models presented in Chael et al (2018a) fit the 1.3 mm constraints and mostly fit the 3 mm image-domain constraints.…”
Section: Constraints On Accretion Flow and Jet Modelsmentioning
confidence: 99%
“…The full range of physical processes that govern dissipation at the smallest scales in hot accretion flows is still unconstrained. In Chael et al (2018a), we investigated two candidates for the origin of viscous dissipation in simulations of Sgr A * : the Landau-damped turbulent cascade heating prescription of Howes (2010) and a prescription for magnetic reconnection heating obtained from particle-in-cell (PIC) simulation data (Rowan et al 2017). We showed that predictions for the image morphology of Sgr A * at 230 GHz and longer wavelengths depend strongly on the choice of heating prescription.…”
Section: Introductionmentioning
confidence: 99%
“…In this paper we present the results of two fully 3D, two-temperature GRRMHD simulations of Magnetically Arrested Discs around the black hole in M87 performed using the code KORAL (Sadowski et al 2013a(Sadowski et al , 2014(Sadowski et al , 2017. In these simulations, we again compare the Landau-damped turbulent cascade heating prescription from Howes (2010) with the magnetic reconnection prescription from Rowan et al (2017); Chael et al (2018a). Both simulations are performed assuming a SMBH mass of 6.2 × 10 9 M (Gebhardt et al 2011, scaled for a distance of 16.7 Mpc; Mei et al 2007) and a dimensionless spin of a = 0.9375.…”
Section: Introductionmentioning
confidence: 99%
“…This means that, for most practical purposes, an "incomplete" equilibrium with T i = T e must be assumed (e.g., Braginskii 1965)-and that is indeed what is observed in the solar wind (see, e.g., Cranmer et al 2009, and references therein). It is not, however, known what determines the ratio T i /T e -a question that is also of great interest in the context of extragalactic plasmas, e.g., accretion discs, where only T e is measured, but knowledge of T i is required for the understanding of basic plasma processes and model building (e.g., Quataert 2003;Sharma et al 2007;Ressler et al 2017;Rowan et al 2017Rowan et al , 2019Chael et al 2018b,a;Chandran et al 2018).…”
Section: Introductionmentioning
confidence: 99%